2009
DOI: 10.1158/1078-0432.ccr-08-2217
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Curcumin in Patients with Monoclonal Gammopathy of Undefined Significance—Its Effect on Paraproteinemia and the Urinary N-Telopeptide of Type I Collagen Bone Turnover Marker

Abstract: Purpose: To determine the effect of curcumin on plasma cells and osteoclasts in patients with MGUS. Experimental Design: Twenty-six patients with MGUS were recruited into the study and administered 4 grams/day oral curcumin. Blood and urine samples were collected at specified visits after initiating therapy. Full blood count, B2 microglobulin, serum paraprotein, and immunoglobulin electrophoresis (IEPG and EPG) were determined for all patients at each visit. Serum calcium, 25 hydroxyvitamin D3, and bone-specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 19 publications
2
71
0
1
Order By: Relevance
“…Both these patients showed a continued improvement in several markers of their disease activity and in particular, a decrease in % plasma cells in the bone marrow. These data are in accordance with our previous findings [5,6] . Although myeloma is a "patchy" disease, the bone histopathology failed to demonstrate progression of the disease, but suggested an improvement in the plasma cell infiltrate.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Both these patients showed a continued improvement in several markers of their disease activity and in particular, a decrease in % plasma cells in the bone marrow. These data are in accordance with our previous findings [5,6] . Although myeloma is a "patchy" disease, the bone histopathology failed to demonstrate progression of the disease, but suggested an improvement in the plasma cell infiltrate.…”
Section: Discussionsupporting
confidence: 94%
“…The most active component in turmeric is curcumin [2] . Based on its demonstrated anti-myeloma cell activity, both in vitro and in vivo [3,4] , we have carried out both a 6 month pilot study [5] and a 6 month randomised, double-blind placebo-controlled cross-over 4g study and a 3 month open-label 8g extension study [6] and shown that oral curcumin can, in a select group of MGUS and SMM patients, decrease free light chains (rFLC, dFLC and iFLC), paraprotein and bone resorption. Here, we present a report of two patients with SMM who were recruited into our second study [6] and who elected to continue on the same regimen of oral curcumin daily after the study.…”
Section: Introductionmentioning
confidence: 99%
“…U 1/ 2 pa cientů, u kterých byla sérová hladina paraproteinu na začátku terapie > 20 g/ l, došlo k jeho poklesu o 12-30 %. Navíc 27 % pa cientů mělo v moči o 25 % nižší koncentraci osteoresorpčního markeru N-terminálního telopeptidu kolagenu typu I [46]. Zdá se tedy, že kurkumin může alespoň částečně blokovat osteoresorpci a snižovat tak pravděpodobnost fraktur.…”
Section: Interakce Kurkuminu a Onkologické Léčbyunclassified
“…More recently, Golombick and Diamond (2) and Golombick et al (3) reported the results of pilot studies which indicated that curcumin, in some patients with monoclonal gammopathy of undetermined significance (MGUS), decreases the paraprotein load and the urinary n-telopeptide of type 1 collagen bone turnover marker. MGUS indicates the presence of a monoclonal (M-) protein in individuals without evidence of multiple myeloma, Waldenström's macroglobulinemia, primary amyloidosis, or related disorders (4).…”
Section: Introductionmentioning
confidence: 99%
“…in a commentary on the above-mentioned study by Golombick et al (3), rajkumar emphasized the crucial importance of developing new methods to prevent the malignant progression of MGUS (11). As mentioned, MGUS often does not present symptoms, while progression leads to incurable disease.…”
Section: Introductionmentioning
confidence: 99%